Unloaded speed of shortening in voltage-clamped intact skeletal muscle fibers from wt, mdx, and transgenic minidystrophin mice using a novel high-speed acquisition system. - Friedrich, Oliver; Weber, Cornelia; von Wegner, Frederic; Chamberlain, Jeffrey S.; Fink, Rainer (Biophysical Journal, 2008)
Skeletal muscle unloaded shortening has been indirectly determined in the past. Here, we present a novel high-speed optical tracking technique that allows recording of unloaded shortening in single intact, voltage-clamped mammalian skeletal muscle fibers with 2-ms time resolution. L-type Ca(2+) currents were simultaneously recorded. The time course of shortening was biexponential: a fast initial phase, tau(1), and a slower successive phase, tau(2,) with activation energies of 59 kJ/mol and 47 kJ/mol. Maximum unloaded shortening speed, v(u,max), was faster than that derived using other techniques, e.g., approximately 14.0 L(0) s(-1) at 30 degrees C. Our technique also allowed direct determination of shortening acceleration. We applied our technique to single fibers from C57 wild-type, dystrophic mdx, and minidystrophin-expressing mice to test whether unloaded shortening was affected in the pathophysiological mechanism of Duchenne muscular dystrophy. v(u,max) and a(u,max) values were not significantly different in the three strains, whereas tau(1) and tau(2) were increased in mdx fibers. The results were complemented by myosin heavy and light chain (MLC) determinations that showed the same myosin heavy chain IIA profiles in the interossei muscles from the different strains. In mdx muscle, MLC-1f was significantly increased and MLC-2f and MLC-3f somewhat reduced. Fast initial active shortening seems almost unaffected in mdx muscle.